Optimal Power Dispatch in Deregulated Environment - Sharma, Nishu (My University, 2010)
The deregulation of the electric power industry is one of the important aspect in power sector. The deregulation of the electric power industry is intended to create market conditions, competitions and innovation etc. Under deregulation, among various issues, managing dispatch is an important control activity in a power system. The control variables has to be obtained by optimizing different objectives of choice by satisfying the power flow. In this thesis, bilateral transactions and multilateral transactions, which are likely to occur in deregulated energy markets, are simulated. The Particle Swarm Optimization (PSO) is applied to obtain optimal dispatch problem with bilateral and multilateral transactions. The performance is studied on IEEE 30 bus system for fuel cost minimization, minimization of active power loss and reactive power loss by considering real power generation and bus voltages as control variables. Generators with exponential and quadratic cost characteristics have been used.
Keywords: Optimal power flow; PSO; Deregulation; Bilateral dispatch; Multilateral dispatch